The Hypoxia-Activated Prodrug TH-302: Exploiting Hypoxia in Cancer Therapy - Li, Yue; Zhao, Long; Li, Xiao-Feng (Frontiers in Pharmacology, 2021)
Hypoxia is an important feature of most solid tumors, conferring resistance to radiation and many forms of chemotherapy. However, it is possible to exploit the presence of tumor hypoxia with hypoxia-activated prodrugs (HAPs), agents that in low oxygen conditions undergo bioreduction to yield cytotoxic metabolites. Although many such agents have been developed, we will focus here on TH-302. TH-302 has been extensively studied, and we discuss its mechanism of action, as well as its efficacy in preclinical and clinical studies, with the aim of identifying future research directions.